2006
DOI: 10.1007/s00167-006-0097-7
|View full text |Cite
|
Sign up to set email alerts
|

Tibial plateau stress fracture after unicondylar knee arthroplasty using a navigation system: two case reports

Abstract: Satisfactory alignments of components in total knee arthroplasty have been reported since the introduction of navigation systems. And thus, such techniques have been introduced for minimally invasive unicondylar knee arthroplasty (UKA). Several intraoperative fractures of the tibial plateau have been reported in association with minimally invasive UKA and some stress fractures of tibial plateau associated with design of instrument have been reported. Here, we report on two cases of stress fracture of the tibia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 11 publications
(23 reference statements)
0
29
0
Order By: Relevance
“…One study reported that navigation leads to less blood loss than traditional instrumentation (Chauhan et al, 2004). The majority of studies have reported no complications (e.g., fracture, infection) from bone screws that attach the optical reference frames to the bone (Stulberg et al, 2002;Hart et al, 2003;Stulberg, 2003;Chauhan et al, 2004;Bolognesi and Hofmann, 2005), although isolated incidences of delayed wound healing and infection (Krackow et al, 2003;Sparmann et al, 2003) and stress fractures (Ossendorf et al, 2006;Seon et al, 2006) occur.…”
Section: Article In Pressmentioning
confidence: 95%
“…One study reported that navigation leads to less blood loss than traditional instrumentation (Chauhan et al, 2004). The majority of studies have reported no complications (e.g., fracture, infection) from bone screws that attach the optical reference frames to the bone (Stulberg et al, 2002;Hart et al, 2003;Stulberg, 2003;Chauhan et al, 2004;Bolognesi and Hofmann, 2005), although isolated incidences of delayed wound healing and infection (Krackow et al, 2003;Sparmann et al, 2003) and stress fractures (Ossendorf et al, 2006;Seon et al, 2006) occur.…”
Section: Article In Pressmentioning
confidence: 95%
“…Any navigation used should be noted as the sites for insertion of the pins can be a source of stress fracture and pain. 2,3 Problems or complications at operation and during the early post-operative recovery period must be identified. It should be established whether the patient complied with the programme of rehabilitation.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…One-stage long-stem TKA restores limb alignment and facilitates fracture healing, with excellent outcome. [1][2][3] and rheumatoid arthritis, 4,5 osteoarthritis, [6][7][8] osteoporosis, 1 post-traumatic deformity, 9 deformed degenerate knees, 4,10 Paget's disease, 11 pyrophosphate arthropathy, 12 and knee arthroplasty (unicondylar and navigated) [13][14][15][16] in elderly people. Stress fractures are usually treated by rest and/or casting 6,10,17 and rarely surgery.…”
mentioning
confidence: 99%